Empirical tests using search engine optimisation techniques to compare the effectiveness of two metadata vocabularies for geospatial data discovery on the Web - Coetzee, Serena Martha (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2015.